The Influence of Leadership Style on Public Sector Employee Performance - Suwardhi Pantih; Akhsanul Khaq; Suwarno Suwarno (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The success of public sector organizations in achieving optimal performance is greatly influenced by leadership style and employee work motivation. However, challenges still exist in implementing effective leadership and adequate motivation to improve employee performance in the public sector. This study aims to examine the effect of leadership style on employee performance with work motivation as a mediating variable. A quantitative approach was used to provide an objective and measurable overview of the relationships among variables. Data were collected through a questionnaire using a five-point Likert scale from all employees of Central Sulawesi, involving 172 respondents through a saturated sampling technique. Data analysis was carried out using SmartPLS 3 software with path analysis to test both direct and indirect effects among the variables. The results showed that leadership style significantly influences work motivation, and work motivation significantly affects employee performance. Furthermore, work motivation was found to significantly mediate the relationship between leadership style and employee performance, while the direct effect of leadership style on employee performance was not statistically significant. These findings highlight the crucial role of work motivation as a bridge between leadership and performance improvement in public sector organizations.